Illich's Omnicompetent Individual: A Process Perspective - Creighton Peden (Educational Considerations, 1976)
Is education structured only to manipulate the individual through an initiation rite into the acquisitive society asks Peden in an article adapted from a paper he gave at the World Congress of Philosophy in Delhi, India.